Insect repellents - what are they and how are they registered? - Steinke, T. L., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2004)
This fact sheet describes what insect repellents are and how they registered nationally and in the state of Colorado.
CEPEP 11/04.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Insect antifeedants -- Safety measures; Insect baits and repellents -- Safety measures